پاکستانی قانون وراثت کے مسائل اور اسلامی احکام: تجزیاتی جائزہ: Pakistani Inheritance Law Issues and Islamic Injunctions: An Analytical Overview - Dr. Majid Rashid; Zia ur Rehman (International Research Journal of Arabic and Islamic Studies, 2024)
Inheritance laws in Pakistan are predominantly governed by Islamic principles as enshrined in the Quran and Hadith, ensuring a structured distribution of a deceased person's estate among heirs. This paper provides an analytical overview of the issues arising from the intersection of Pakistani inheritance law and Islamic injunctions. It explores the legal framework of inheritance in Pakistan, the Islamic jurisprudential basis, and the practical challenges faced by individuals. Issues such as gender inequality, testamentary freedom, and the lack of awareness about inheritance rights are examined. The analysis reveals that while the Islamic legal framework aims to ensure fairness and justice, its implementation in Pakistan often falls short due to socio-cultural practices and legal loopholes. Recommendations are provided to address these issues, emphasizing the need for legal reforms, public awareness campaigns, and a more robust implementation of Islamic inheritance laws to achieve the intended justice and equity.